A method to characterize the quality of a polymer laser sintering process - Rüsenberg, Stefan; Josupeit, Stefan; Schmid, Hans-Joachim (Advances in Mechanical Engineering)
The reproducibility and reliability of quality aspects are an important challenge of the polymer laser sintering process. However, existing quality concepts and standardization activities considering influencing factors along the whole process chain have not been validated experimentally yet. In this work, these factors are analyzed and kept constant to obtain a reliable material data set for different layer thicknesses and testing temperatures. In addition, material qualities regarding powder ageing effects are analyzed using different build heights and layer thicknesses: while an increase of the layer thickness reduces mechanical part strength and density, it also results in a less intense thermal ageing of unmolten powder due to shorter build times.

Development of a Basic Model to Simulate the Laser Sintering Cooling Process - Josupeit, Stefan; Ordia, L.; Schmid, Hans-Joachim (International Conference on Additive Technologies)
The process-related occurrence of varying cooling rates at different positions within the part cake is an important challenge regarding the part quality and reproducibility of the polymer laser sintering process. Temperature history dependent parameters are for example the part warpage, the crystallization behavior or powder ageing effects, which have to be considered for optimized process controls. Nevertheless, the inner temperature distribution and history during the cooling process is difficult to measure and less known yet. In this work, a Finite Element (FE) model is developed to understand and predict the temperature distribution and history within the part cake during the cooling process. Therefore, the thermal boundary conditions of a laser sintering system are analyzed and relevant parameters are identified. A basic FE model is set up in ABAQUS CAE software considering a part-free powder cake. Important thermal parameters of the bulk powder and the environment are adjusted and verified in relation to experimental in-process measured data. With this model it is possible to predict position-dependent cooling rates as a function of significant job parameters, for example the job height or the environmental conditions during the cooling phase. In combination with extended in-process temperature measurements and a consideration of built parts, this model will be an important tool for the development of optimized process controls.

Simulation of the Surface Topography on Laser Sintered Polymer Parts - Delfs, Patrick; Schmid, Hans-Joachim (25th Annual International Solid Freeform Fabrication Symposium)
One barrier of laser sintering (LS) to become the main process for Direct Manufacturing (DM) is the surface quality of LS parts. Hence, the property which has to be improved is the rough surfaces of LS parts due to the layered structure. Another additional effect is the incomplete melting of powder particles on the surface due to the high process temperature. In this paper we demonstrate our approach of a theoretical model for the topography of LS part surfaces. We investigated the surface roughness as a function of surface orientation. Considering that the model involves further variables as layer thickness, particle density and particle size distribution to describe the topography precisely. Experimental results were used to optimize and check the results of the model.

Extension of prior developed design rules (LS) - Adam, Guido; Zimmer, Detmar (ASPE - Spring topical meeting 2014)

Systematic investigations of minimum feature sizes and geometrical accuracies - Adam, Guido; Zimmer, Detmar

Design for Additive Manufacturing - Element transitions and aggregated structures - Adam, Guido; Zimmer, Detmar (CIRP Journal of Manufacturing Science and Technology)
Additive Manufacturing technologies create parts layer by layer. Thereby, lots of benefits are offered. Especially extended design freedoms provide new potentials for the design of technical parts. To make these benefits accessible to different user groups, design rules for Additive Manufacturing were developed within the project ‘‘Direct Manufacturing Design Rules’’. Therefore a process independent method was defined first. Next, design rules were developed for Laser Sintering, Laser Melting and Fused Deposition Modeling. The results were summarized in a design rule catalog and support a suitable design for Additive Manufacturing

Erweiterung des Gültigkeitsbereichs von Konstruktionsregeln beim Lasersintern - Adam, Guido

Extension of prior developed design rules for laser sintering - Adam, Guido

Data Acquisition and Signal Analysis from Measured Motor Currents for Defect Detection in Electromechanical Drive Systems - Lessmeier, Christian; Enge-Rosenblatt, Olaf; Bayer, Christian; Zimmer, Detmar (European Conference of the PHM Society 2014 (EPHM14))

Auswahl anwendungsoptimaler Antriebssysteme als Basis für die Komposition von Antriebsbaukästen - Klause, Alexander; Zimmer, Detmar (Entwerfen - Entwickeln - Erleben 2014. Beiträge zur virtuellen Produktentwicklung und Konstruktionstechnik)

Intelligent Operating Strategies for Multi-Motor Drive Systems - Strop, Malte; Hölscher, Christian; Zimmer, Detmar (OPT-i 2014. 1st International Conference on Engineering and Applied Sciences Optimization)

Intelligente Betriebsstrategien für Mehrmotorenantriebssysteme - Zimmer, Detmar; Hölscher, Christian; Strop, Malte (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Konzeption von Antriebssystembaukästen auf der Basis von branchenspezifischen Antriebslösungen - Klause, Alexander; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

intelligent Drive Module (iDM) - Hölscher, Christian; Zimmer, Detmar

Application of Self-optimizing Systems - Hölscher, Christian; Keßler, Jan Henning; Meyer, Tobias; Rasche, Christoph; Reinold, Peter; Sextro, Walter

Molecular Processes Studied at a Single-Molecule Level Using DNA Origami Nanostructures and Atomic Force Microscopy - Bald, Ilko; Keller, Adrian (Molecules)

SeSAME: Modeling and Analyzing High-Quality Service Compositions - Arifulina, Svetlana; Becker, Matthias; Platenius, Marie Christin; Walther, Sven ({Proceedings of the 29th IEEE/ACM International Conference on Automated Software Engineering (ASE 2014)})
Today, software components are traded on markets in form of services. These services can also be service compositions consisting of several services. If a software architect wants to provide such a service composition in the market for trade, she needs to perform several tasks: she needs to model the composition, to discover existing services to be part of that composition, and to analyze the composition's functional correctness as well as its quality, e.g., performance. Up to now, the architect needed to find and use different tools for these tasks. Typically, these tools are not interoperable with each other. We provide the tool SeSAME that supports a software architect in all of these tasks. SeSAME is an integrated Eclipse-based tool-suite providing a comprehensive service specification language to model service compositions and existing services. Furthermore, it includes modules for service matching, functional analysis, and non-functional analysis. SeSAME is the first tool that integrates all these tasks into one tool-suite and, thereby, provides holistic support for trading software services. Thus, it contributes to a software provider's market success.

Towards Systematic Configuration for Architecture Validation - Becker, Matthias; Becker, Steffen; Besova, Galina; Walther, Sven; Wehrheim, Heike ({Proceedings of the 40th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) (Work in Progress Session)})

Cloud Computing Reduces Uncertainties in Quality-of-Service Matching! - Becker, Matthias; Platenius, Marie Christin; Becker, Steffen ({Proceedings of the 2nd International Workshop on Cloud Service Brokerage (CSB)})
Cloud computing resulted in a continuously growing number of provided software services to be used by consumers. Brokers discover services that fit best to consumers' requirements by matching Qualityof-Service (QoS) properties. In order to negotiate Service-Level Agreements (SLAs), a provider has to determine the provided QoS based on QoS analyses. However, the risk for the provider to violate the SLA is high as the service's actual quality can deviate from the specified QoS due to uncertainties that occur during the provider's quality analysis. In this paper, we discuss current software engineering paradigms like cloud computing and service-oriented computing with respect to the amount of uncertainty they induce into service matching and SLA negotiations. As a result, we explain, why cloud computing reduces such uncertainties.

2.3 Artifact-Centric Requirements Engineering for Self-Adaptive Systems - Knauss, Alessia; Muñoz-Fernández, Juan C.; Castañeda, Lorena; Becker, Matthias; Derakhshanmanesh, Mahdi; Taherimakhsousi, Nina; Heinrich, Robert ({Report from the GI Dagstuhl Seminar 14433: Software Engineering for Self-Adaptive Systems})

Approaching the Cloud: Using Palladio for Scalability, Elasticity, and Efficiency Analyses - Lehrig, Sebastian; Becker, Matthias ({Proceedings of the Symposium on Software Performance (SOSP)})

Feature models supporting trade-off decisions in early mechatronic systems design - Kühn, Arno; Bremer, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (NordDesign 2014, Espoo, Finnland, 27. - 29. Aug. 2014)

Der Spitzencluster it's OWL auf dem Weg zur Industrie 4.0 - Gausemeier, Jürgen; Dumitrescu, Roman; Jasperneite, Jürgen; Kühn, Arno; Trsek, Henning (ZWF - Zeitschrift für Wirtschaftlichen Fabrikbetrieb)

Terrain Classification for Track-driven Agricultural Robots - Mahadhir, Khairul Azmi; Tan, Shing Chiang; Low, Cheng; Dumitrescu, Roman; Amin, Adam Tan Mohd; Jaffar, Ahmed (Procedia Technology)

Specification Technique CONSENS for the Description of Self-optimizing Systems - Dorociak, Rafal; Dumitrescu, Roman; Gausemeier, Jürgen; Iwanek, Peter (Design Methodology for Intelligent Technichal Systems)

Strategy controlling for innovation clusters - the example of "it's OWL" - Kühn, Arno; Kliewe, Daniel; Dumitrescu, Roman; Gausemeier, Jürgen (ISPIM Conference 2014)

Systematische Berücksichtigung von Fertigungsanforderungen im Model-Based Systems Engineering - Dumitrescu, Roman; Fechtelpeter, Christian; Kühn, Arno (Tag des Systems Engineering, Bremen)

Methodology for the identification of solution patterns within mechatronic systems - Rabe, Martin; Anacker, Harald; Dumitrescu, Roman (Proceedings of the 15th International Workshop on Research and Education in Mechatronics (REM), El Gouna, Egypt)

Collaboration in Model-Based Systems Engineering based on Application Scenarios - Tschirner, Christian; Kaiser, Lydia; Dumitrescu, Roman; Gausemeier, Jürgen (NordDesign 2014)

Optimized process sequences for prototyping of molded interconnect devices - Jürgenhake, Christoph; Fechtelpeter, Christian; Dumitrescu, Roman; Heidsiek, Daniel (Advanced Materials Research)

Method for the Identification and Comparison of Alternative Process Chains Focusing on Economics Efficiency Analysis during the Conceptual Design of Mechatronic Integrated Devices - Schierbaum, Thomas; Gausemeier, Jürgen; Dumitrescu, Roman (Advanced Materials Research)

Virtual Commissioning by Means of an Adaptive Selection of the Modeling Depth - Frieben, Tanja; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE14, Montreal, Québec, Canada)

Methodology for a Partly Automated Parameter Identification for the Validation of Multi-Domain Models - Kruse, Daniel; Schweers, Christoph; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Dynamic Behavior Models and their Modeling Depth in the Design Process of Mechatronic Systems - Lochbichler, Matthias; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Ansätze zur Regelung eines elektronischen Lastemulators für die Hardware-in-the-Loop-Simulation von Antriebsreglern auf Leistungsebene - Kromov, Ivan; Deter, Matthias; Trächtler, Ansgar (SPS IPC Drives)

Optimal Trajectory Planning for Robotic Manipulators Using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Multi-Conference on Systems and Control (MSC) / 23rd Conference on Control Applications (CCA))

Analysis of high speed bending operations as basis for integrating self-correcting components to increase process reliability - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Homberg, Werner; Trächtler, Ansgar (Procedia Engineering 81)

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin (Workshop GMA-Fachausschuss 1.30)

Subjective Evaluation of Different Motion Cueing Algorithms Implemented on ATMOS Driving Simulator - Al Qaisi, Imad; Zimmermann, Daniel; Kohlstedt, Andreas; Gausemeier, Sandra; Trächtler, Ansgar (Driving Simulation Conference 2014)

Consensus coordination for multiple autonomous intersection management - Wuthishuwong, Chairit; Trächtler, Ansgar (Tagungsband 9. Dortmunder AutoTag)

Modellbasierte Analyse und regelungstechnische Maßnahmen zur Optimierung des Vereinzelungsvorgangs in Bankautomaten - Just, Viktor

Stability of the consensus in the network of multiple Autonomous Intersections Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 20th International Conference on Automation and Computing (ICAC))

Simultaneous Path Planning and Trajectory Optimization for Robotic Manipulators using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Robotica)

Consensus Coordination in the Network of Autonomous Intersection Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 11th International Conference on Informatics in Control Automation and Robotics ICINCO)

Sliding Mode and Continuous Estimation Techniques for the Realization of Advanced Control Strategies for Parallel Kinematics - Flottmeier, Sarah; Olma, Simon; Trächtler, Ansgar (Proceedings of the 19th IFAC World Congress)

Control of Pareto Points for Self-Optimizing Systems with Limited Objective Values - Kessler, Jan Henning; Trächtler, Ansgar (The 19th IFAC World Congress)

Joint Selection Criterion for Optimal Trajectory Planning for Robotic Manipulators Using Dynamic Programming - Shareef, Zeeshan; Trächtler, Ansgar (19th IFAC World Congress)

Analyses of the stress-strain behaviour of SMAs under cyclical loading conditions – implementation of a novel phenomenological constitutive model - Pai, Arathi; Krooß, Philipp; Niendorf, Thomas; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (Posterbeitrag ICOMAT - International Conference on Martensitic Transformations, Juli 2014, Bilbao, Spanien)

Concept for a self-correcting sheet metal bending operation

Design and Control of a Vertical Ball Juggling Delta Robot without Visual Guidance - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Trächtler, Ansgar (13th International Conference on Intelligent Autonomous Systems)